2002
DOI: 10.1046/j.1365-313x.2002.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Arabidopsis nuclear gibberellin signalling protein GAI is not destabilised by gibberellin

Abstract: SummaryPlant growth is regulated by bioactive gibberellin (GA), although there is an unexplained diversity in the magnitude of the GA responses exhibited by different plant species. GA acts via a group of orthologous proteins known as the DELLA proteins. The Arabidopsis genome contains genes encoding five different DELLA proteins, the best known of which are GAI and RGA. The DELLA proteins are thought to act as repressors of GA-regulated processes, whilst GA is thought to act as a negative regulator of DELLA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 45 publications
2
65
2
1
Order By: Relevance
“…In this article, we demonstrate that SLY1 interacts not only with RGA, but also with GAI through their GRAS domains. In contrast with a previous study (Fleck and Harberd, 2002), we show that GA induces degradation of the endogenous GAI protein and that the sly1-10 mutant accumulates a significantly higher amount of GAI than in the wild type. The rga and gai null alleles synergistically suppress several GA-mediated processes in sly1-10.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this article, we demonstrate that SLY1 interacts not only with RGA, but also with GAI through their GRAS domains. In contrast with a previous study (Fleck and Harberd, 2002), we show that GA induces degradation of the endogenous GAI protein and that the sly1-10 mutant accumulates a significantly higher amount of GAI than in the wild type. The rga and gai null alleles synergistically suppress several GA-mediated processes in sly1-10.…”
Section: Introductioncontrasting
confidence: 99%
“…Although a previous study showed that levels of a GAI-GFP fusion were not reduced by GA treatment (Fleck and Harberd, 2002), we decided to use immunoblot analysis to examine whether endogenous GAI protein level is elevated in the sly1-10 mutant background and whether GA treatment induces a rapid reduction in GAI protein levels in the wild-type SLY1 background. The predicted molecular masses of RGA and GAI are 64 and 59 kD, respectively.…”
Section: Regulation Of Ga-induced Gai Degradation By Sly1mentioning
confidence: 99%
See 1 more Smart Citation
“…GA relieves DELLA restraint by promoting the disappearance of nuclear DELLAs (Silverstone et al, 2001;Fleck and Harberd, 2002). In Arabidopsis, GA is detected by the GA receptor AtGID1 (Nakajima et al, 2006).…”
mentioning
confidence: 99%
“…In addition, one or two putative nuclear localization signals are present in some of the GRAS members, suggesting that they may function as transcriptional regulators (Pysh et 1999). Indeed, several DELLA proteins, when fused with the green fluorescence protein, are localized to the nuclei in transgenic plants (Silverstone et al, 2001;Fleck and Harberd, 2002;Gubler et al, 2002;Itoh et al, 2002;Wen and Chang, 2002).…”
mentioning
confidence: 99%